2000
DOI: 10.1034/j.1399-0004.2000.570506.x
|View full text |Cite
|
Sign up to set email alerts
|

Aberrant SP‐B mRNA in lung tissue of patients with congenital alveolar proteinosis (CAP)

Abstract: Mutations in the surfactant protein (SP)-B gene are responsible for SP-B deficiency in congenital alveolar proteinosis (CAP) (Nogee et al. J Clin Invest 1994: 93: 1860-1883; Lin et al. Mol Genet Metab 1998: 64: 25-35; Klein et al. Pediatrics 1998: 132: 244-248; Ballard et al. Pediatrics 1995: 96: 1046-1052). The multigenerational consanguineous pedigree under study does not carry any of the known mutations, although this pedigree had 14 infant deaths following respiratory distress at birth. Immunostaining of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(45 citation statements)
references
References 32 publications
0
45
0
Order By: Relevance
“…Such an alteration eliminates a potential site of glycosylation and is associated with certain pulmonary pathologies. 44 WANG et al 57 confirmed the existence of an N-linked glycosylation site at the terminal portion of SP-B gene. The T allele of the polymorphism 1580 (C/T) does not have the N-linked glycosylation site at the N-terminal fragment, and it is considered a protector factor regarding RDS, whereas the allelic variant C, which contains the recognition N glycosylation site of the fragment N-terminal, is a risk factor for chronic obstructive pulmonary disease (COPD) and ARDS.…”
Section: Genetic Factors Of Respiratory Distress Syndromementioning
confidence: 71%
See 1 more Smart Citation
“…Such an alteration eliminates a potential site of glycosylation and is associated with certain pulmonary pathologies. 44 WANG et al 57 confirmed the existence of an N-linked glycosylation site at the terminal portion of SP-B gene. The T allele of the polymorphism 1580 (C/T) does not have the N-linked glycosylation site at the N-terminal fragment, and it is considered a protector factor regarding RDS, whereas the allelic variant C, which contains the recognition N glycosylation site of the fragment N-terminal, is a risk factor for chronic obstructive pulmonary disease (COPD) and ARDS.…”
Section: Genetic Factors Of Respiratory Distress Syndromementioning
confidence: 71%
“…After 2 years, Lin et al published a study of a family with a history of 14 newborn deaths due to early respiratory insufficiency. 44 The immunohistochemistry of the lung from 3 of these children showed a decrease or absence of SP-B expression. Nine polymorphisms were found in this family, but it was not possible to attribute any of them to the SP-B deficiency.…”
Section: Surfactant Proteins: Genetic Determinants and Pulmonary Disementioning
confidence: 99%
“…Although it is located outside the protein translation site, this region can somehow impact gene expression and/or protein function (24).…”
Section: Discussionmentioning
confidence: 99%
“…For amplification of the segments that span the polymorphisms mentioned previously, we used previously described primers and protocols (23,24). All primers used are listed in Table 2.…”
Section: Laboratory Testsmentioning
confidence: 99%
See 1 more Smart Citation